Relevansi Nilai-Nilai Etika Kristiani Dalam Kehidupan Masyarakat Global - Alfons Seran (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This article deals with our plural and global society of today which impede the validity of ethical values. In this sense, the values of Christian ethics are needed to approach contemporary social issue. We must respond to the current situation of humanity by using library resources and observations of ethical issue in our society and how they can develop their normative effects under the conditions of freedom, plurality, demographic and digital change, as well as the complex economic and financial systems and, last but not least, under the fragile approval of the institutions of international politics. The argument then moves to the meta-theory of Christian ethics, namely the revelation of God as it is expressed in the ‘book of nature’, the written word, and the incarnate Word, Jesus Christ. The article concludes that as long as the values of Christian ethics remains faithful to this meta-theory, understands the modern macro-ethical questions and maintains a deep social focus, it will remain relevant in a plural and global society.